Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.21608/misrj.2018.12824
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Safety Assessment of a Printing Plant in Cairo, Egypt

Abstract: Background: The workplace environment impacts workers health, morale, productivity and engagement-both positively and negatively. The workplace environment in most of industry is unsafe and unhealthy. During the past ten years, the printing services have met a large development. Technological changes and the introduction of new work processes in the matter of printing have had a deep impact on labor, security and health. Objectives: to describe the environmental features of a printing press in Cairo. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Printing and photocopy workers being generally exposed to many hazardous materials which might lead to various health issues. (17,22) In referral to demographic characteristics of the studied workers in the present study, the mean age of studied workers was (mean± SD) 43.06 ± 8.59 (27.0-59.0), this result came to an agreement with Ibrahim et al, (13); Who informed that the mean age was (mean± SD) 42.65 ± 9.33.…”
Section: Discussionsupporting
confidence: 90%
“…Printing and photocopy workers being generally exposed to many hazardous materials which might lead to various health issues. (17,22) In referral to demographic characteristics of the studied workers in the present study, the mean age of studied workers was (mean± SD) 43.06 ± 8.59 (27.0-59.0), this result came to an agreement with Ibrahim et al, (13); Who informed that the mean age was (mean± SD) 42.65 ± 9.33.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning the correlation occupational health hazards and safety measures, the results of this study found that a negative statistically significant correlation between total occupational hazards and total safety measures, this means when the protective measures are used in the workplace and the workers had training and follow the guidelines and rules for safety measures those will lead to the decline of occupational hazards that affect on workers' health. In similarity to the previous study done in Cairo by Ibrahim et al (2018) [18] who stated adequate preventive and control measures in the work environment are leading decrease work hazards also authors found wearing protective clothes, good ventilation and lighting in the printing shop were statistically significantly associated with a lower prevalence of occupational hazards. According to the results of this study, there were statistically significant differences in relationships between genders, age, and year of work experiences in relation to total injuries, chemical hazards subscale.…”
Section: Discussionsupporting
confidence: 84%